Protease of Euphorbea pilulifera - Khan, M.R.; Iqbal, Z. (Asian Journal of Chemistry, 2011)
The content and characteristics of the protease present in the plant tissue of Euphorbia pilulifera, a latex plant commonly encountered in Pakistan as Dhokak were studied. The whole plant tissue was found rich in protease activity. It contained 9.6 units/g protease activity in the whole plant tissue. The data on crude state characteristics of the protease of Euphorbia pilulifera indicated that its crude extract contained acid, alkaline and neutral proteases. One of the enzyme components was thermo-labile that started deactivating at 40 ºC and another one thermo-stable, which started denaturing at 70 ºC. These indications were supported by the pH-profile of the crude enzyme and also by the pH-stability trends of the enzyme components. These profiles indicated that the dominant protease was neutral. The alkaline protease fell next in order, while acid protease seed to be present in small amount.